2008
DOI: 10.1245/s10434-008-0021-0
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Outcomes Associated with Noncompliance with Melanoma Treatment Guidelines

Abstract: While there are valid reasons for variance from treatment algorithms, these data suggest that compliance with NCCN guidelines improves outcome and decreases morbidity in clinically node-negative melanoma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…This study also noted variation in compliance based on geographic area and improved compliance over time during the 4‐year study period. Similar findings with respect to excision margins were published in 2008 from a single teaching institution experience demonstrating that 87% of patients with in‐situ and thin melanomas, yet only 60% of patients with T2‐T4 primaries, received guideline‐appropriate margins of excision 89. Findings obtained from querying the National Cancer Database (NCDB) of the American College of Surgeons demonstrated that of 8,525 patients with clinical stage IB/II disease, 48.7% underwent SLN biopsy 90.…”
Section: Compliance With Guidelines: How We Are Doing and Concluding supporting
confidence: 80%
See 2 more Smart Citations
“…This study also noted variation in compliance based on geographic area and improved compliance over time during the 4‐year study period. Similar findings with respect to excision margins were published in 2008 from a single teaching institution experience demonstrating that 87% of patients with in‐situ and thin melanomas, yet only 60% of patients with T2‐T4 primaries, received guideline‐appropriate margins of excision 89. Findings obtained from querying the National Cancer Database (NCDB) of the American College of Surgeons demonstrated that of 8,525 patients with clinical stage IB/II disease, 48.7% underwent SLN biopsy 90.…”
Section: Compliance With Guidelines: How We Are Doing and Concluding supporting
confidence: 80%
“…This study revealed that in terms of compliance with excision margins, non‐compliant treatment was associated with a 17% complication rate—3.4‐fold higher than the overall complication rate. Furthermore, local and regional relapse as the first site of failure was higher in the stage I and II patients who received initial non‐compliant management: 24% versus 6% for patients categorized as non‐compliant vs compliant, respectively 89.…”
Section: Compliance With Guidelines: How We Are Doing and Concluding mentioning
confidence: 94%
See 1 more Smart Citation
“…Both underutilization of evidence-based care and overutilization of unnecessary services have been documented 3–18. The former can lead to worse cancer outcomes, whereas the latter increases the cost of care without increasing value 16. To address these concerns across all specialties, the American Board of Internal Medicine (ABIM) Foundation launched an initiative to improve “appropriateness” of medical care in the United States.…”
mentioning
confidence: 99%
“…Several reports measuring adherence to National Comprehensive Cancer Network (NCCN) guidelines have demonstrated a relationship between compliance and improved outcomes in a variety of malignancies, including melanoma, 31 colon cancer, 32,33 pancreatic cancer, 34 gastric cancer, 35 and others. [36][37][38] In an effort to improve adherence to CPGs, multidisciplinary cancer clinics (MDCs) were introduced, which showed higher concordance with published CPGs compared to non-multidisciplinary clinics.…”
mentioning
confidence: 99%